Czy możliwe było odkupienie człowieka bez śmierci krzyżowej Jezusa? - Wilk, Rafał Kazimierz (Collectanea Theologica, 2018)
The author raises the question of whether the redemption of man must have been accomplished through the Passion and Death on a cross of Jesus Christ, or whether it could have been realized by the people’s acceptance of the message of the Gospel. By analyzing the historical aspect, such as understanding the prophecies by the Jews and especially by the Apostles, it seems that the latter was possible. It was only after the rejection of the proclaimed Kingdom of God that the Son of God paid the greatest price – and that is by giving up his life for the redemption of mankind. Romano Guardini favors this solution. The author of the study also shows reasons for opposing opinions which are more deeply rooted in the tradition of preaching. Belonging to this group are, among others, Pope Benedict XVI, who writes that it is not contradictory to maintain that Jesus wanted to reconcile the people with the Father only by accepting the Kingdom proclaimed to them. However, when the people rejected the Gospel which was proclaimed by the One who loved them, he accepted this rejection as well as all its extreme consequences, namely the Passion and Death on a cross. Nevertheless, the Pope writes that this version cannot be proven in any way by referring to the Gospel records. Since there are no sufficient sources of evidence, other schemes of the salvation of humanity apart from the Passion and Death on a cross can only be a hypothesis. Hence, they are just a result of pure speculation, and as such are outlined in this study.